IoT-based Hydroponic Monitoring System - Mohamed Faraish, Rusyaidi Akmal (IRC, 2019)
Internet of Things has made the world more virtually and ease to access the information by the tip of our fingers and advancing tools. For my Final Year Project (FYP), I have come up with an IoT based Hydroponic Monitoring System project that brings benefit to the gardener and people that want to start gardening but busy with their schedule. Hydroponic is one of the gardening techniques that does not use any soil instead used an alternative of nutrient water. This IoT Hydroponic will help the user to control the water pump to supply water nutrient to the plant and control the light to supply the light source to the plant. Internet of Things has been used globally since it is one of the pillars of Industrial Revolution 4.0 that has been used and grown in Malaysia. In conclusion, I believe that this project, IoT Based Hydroponic Monitoring System, will bring benefits to the people that love to garden and want to start gardening so that we can move forward to green city and healthier earth.